2010
DOI: 10.1270/jsbbs.60.233
|View full text |Cite
|
Sign up to set email alerts
|

Influence of puroindoline genotypes on grain characteristics, physico-chemical properties of flour and end-use quality of Korean wheats

Abstract: Puroindoline genotypes, grain characteristics, physico-chemical properties of flour and end-use qualities of Korean wheat cultivars were evaluated to determine the influence of puroindolines genotypes and to provide on those characteristics. Nine Korean wheat cultivars carried Pina-D1a/Pinb-D1a, fourteen had Pina-D1a/ Pinb-D1b, and three had Pina-D1b/Pinb-D1a. Pina-D1b/Pinb-D1a and Pina-D1a/Pinb-D1b genotypes showed significantly higher 1000-kernel weight and hardness index in grain characteristics, higher flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
(48 reference statements)
3
3
0
Order By: Relevance
“…The RF protein values agree with the results obtained by Park et al (2010) and Barros et al (2010). The WF protein values agree with results obtained by Barros et al (2010) and Doblado-Maldonado et al (2012).…”
Section: Flour Chemical Analysissupporting
confidence: 90%
See 2 more Smart Citations
“…The RF protein values agree with the results obtained by Park et al (2010) and Barros et al (2010). The WF protein values agree with results obtained by Barros et al (2010) and Doblado-Maldonado et al (2012).…”
Section: Flour Chemical Analysissupporting
confidence: 90%
“…Park et al (2010) obtained similar ash content values for RF whereas Doblado-Maldonado et al (2012) reported lower ash content for WF than the level found in the present study. The mineral fraction represented by the ash content of wheat was located primarily in the pericarp; therefore, the ash content should be low for RF, indicating low contamination in the milling process (Chiang, Chen, Chang, 2006).…”
Section: Flour Chemical Analysissupporting
confidence: 68%
See 1 more Smart Citation
“…Pancake diameter was negatively correlated with the specific volume of pancake which was highly correlated with the density of batter (Kiszonas et al 2015). No significant relationship was between those parameters because of Korean wheats used in this study carrying soft and hard texture in grain hardness (Park et al 2010). Pancake diameter was negatively correlated with pancake height, which this relationship was agreed with previous report (Bettge 2014).…”
Section: Pancake Qualitysupporting
confidence: 88%
“…The kernel texture is controlled by a major ''hardness'' (Ha) locus, which is found on the short arm of chromosome 5D in bread wheat (Park et al 2010). The ''hardness'' locus has a complex structure that is about 82,000 bp long, which includes the puroindoline genes (Pina and Pinb) and the ''grain softness protein'' gene (Gsp) (Chantret et al 2005).…”
mentioning
confidence: 99%